2009
DOI: 10.7861/clinmedicine.9-4-323
|View full text |Cite
|
Sign up to set email alerts
|

The value of the post-take ward round: are new working patterns compromising junior doctor education?

Abstract: -This prospective observational study assessed the impact of the changes in junior doctors' working hours and waiting-time initiatives on teaching and learning opportunities for junior doctors in acute medicine. An audit cycle of post-take ward rounds including all medical admissions to an urban teaching hospital was conducted. During two sevenday periods in July 2006 and 2008, 317 and 354 patients were admitted respectively. In the two-year interval a number of changes were implemented resulting in a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…Limited senior reviews were captured but this may reflect a bigger problem with team structures. 18 Workload distribution and staffing might have a serious impact on clinical outcomes. Increased consultant presence has been shown to be associated with reduced case-adjusted mortality rates in at least one publication.…”
Section: Discussionmentioning
confidence: 99%
“…Limited senior reviews were captured but this may reflect a bigger problem with team structures. 18 Workload distribution and staffing might have a serious impact on clinical outcomes. Increased consultant presence has been shown to be associated with reduced case-adjusted mortality rates in at least one publication.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Dewhurst promotes the idea that the PTWR provides a range of learning opportunities, but concluded that time constraints and a lack of consultants’ appreciation of the possibilities limits the incorporation into practice . This is supported by a large published audit, showing that target‐driven changes to working practice negatively impacted on training opportunities during the PTWR . These primarily focused on medical education, but ‘teaching time’ could easily be translated to a discussion of the process of leading a ward round.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,10 In the Annual RCPL Registrar Survey 2011, 96% of medical registrars felt that reviewing new admissions that they had assessed on 'the take' with a consultant was important for their training. 11 importance of using learning opportunities in every clinical situation.…”
Section: Discussionmentioning
confidence: 99%